Concise encyclopedia chemistry - Eagleson, Mary (Walter de Gruyter, 1994)
This is more of an encyclopedic dictionary, with many entries having only a one-sentence definition. There is no index. Instead, a see reference is made for a term covered in a longer article. For example, under shoe polish is the reference "see Leather care products." This method works quite well, providing an easy way to locate discussions. The text of each longer entry is well written and understandable to the educated layperson. This book is well illustrated, with many line drawings, tables, and charts.